Lokasi Sekolah, Jenis Kelamin, dan Efektifitas Guru Dalam Mengajar terhadap Prestasi Belajar IPS - Sugianto; Ninik Indawati (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2020)
Potential students can be developed through learning activities at school so that what is the goal of learning can be achieved which is realized in learning achievement. Learning achievement can be used as an indicator of the success of a student in learning activities. This study aims to determine whether there is a simultaneous or partial influence between school location, gender and teacher effectiveness in teaching social studies learning achievement. The method used in this research is quantitative with a type of correlational research involving 55 male students and 67 female students taken using a proportional random sampling technique. The results showed a significant effect simultaneously between school location, gender and teacher effectiveness in teaching social studies learning achievement. Partially the location of the school has an effect on social studies learning achievement. Gender has no effect on social studies learning achievement. The effectiveness of the teacher in teaching influences social studies learning achievement.